2004
DOI: 10.1128/aem.70.8.4458-4467.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Transmission ofListeria monocytogenesInfecting Ruminants and in the Farm Environment

Abstract: A case-control study involving 24 case farms with at least one recent case of listeriosis and 28 matched control farms with no listeriosis cases was conducted to probe the transmission and ecology of Listeria monocytogenes on farms. A total of 528 fecal, 516 feed, and 1,012 environmental soil and water samples were cultured for L. monocytogenes. While the overall prevalence of L. monocytogenes in cattle case farms (24.4%) was similar to that in control farms (20.2%), small-ruminant (goat and sheep) farms showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
316
5
21

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(367 citation statements)
references
References 41 publications
16
316
5
21
Order By: Relevance
“…Moreover, the impact of farming practices on the prevalence of L. monocytogenes has not yet been elucidated. Generally, it has been found that bovine farm environments yield a particularly high prevalence of L. monocytogenes, including subtypes linked to human listeriosis cases and outbreaks (Nightingale et al, 2004). In contrast to small ruminants, cattle appear to contribute to the amplification and spread of L. monocytogenes in the farm environment, which suggests that the epidemiology and transmission of L. monocytogenes could differ between ruminant species (Nightingale et al, 2004;Oliver et al, 2005).…”
Section: The Environment As a Reservoirmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the impact of farming practices on the prevalence of L. monocytogenes has not yet been elucidated. Generally, it has been found that bovine farm environments yield a particularly high prevalence of L. monocytogenes, including subtypes linked to human listeriosis cases and outbreaks (Nightingale et al, 2004). In contrast to small ruminants, cattle appear to contribute to the amplification and spread of L. monocytogenes in the farm environment, which suggests that the epidemiology and transmission of L. monocytogenes could differ between ruminant species (Nightingale et al, 2004;Oliver et al, 2005).…”
Section: The Environment As a Reservoirmentioning
confidence: 99%
“…Generally, it has been found that bovine farm environments yield a particularly high prevalence of L. monocytogenes, including subtypes linked to human listeriosis cases and outbreaks (Nightingale et al, 2004). In contrast to small ruminants, cattle appear to contribute to the amplification and spread of L. monocytogenes in the farm environment, which suggests that the epidemiology and transmission of L. monocytogenes could differ between ruminant species (Nightingale et al, 2004;Oliver et al, 2005). L. monocytogenes in cattle farms has a seasonality pattern with higher environmental isolation rates in spring possibly as a consequence of a combination of winter livestock housing, silage feeding and spring application of manure (Wilkes et al, 2011).…”
Section: The Environment As a Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeria monocytogenes, además de causar graves infecciones en los seres humanos, también se encuentra causando enfermedad invasiva en muchas especies de diferentes de animales, incluidos los rumiantes de granja, como vacas, ovejas y cabras (7). Varios productos alimenticios derivados de estos animales, han sido frecuentemente implicados como fuentes de casos y brotes de listeriosis en humanos (8), ya que el microorganismo presente en las materias primas se puede inactivar eficazmente por las combinaciones de tiempo y temperatura típicas para la producción de alimentos más procesados (por ejemplo, leche pasteurizada), pero es difícil de manejar en productos alimenticios listos para el consumo, los cuales sufren contaminación cruzada con elementos contaminados del entorno de la planta de procesamiento (9) o con las manos de los manipuladores durante el proceso de producción, lo cual se constituye como la primera causa de (10).…”
unclassified
“…Food contamination usually occurs by cross-contamination of the final product by L. monocytogenes present in food processing plant environments. Despite infected animals are infrequently linked to human infections, animal-derived food products not processed before consumption, as well as raw food of plant origin contaminated by manure from infected or shedding animals can directly cause human listeriosis (Nightingale et al 2004).…”
Section: Introductionmentioning
confidence: 99%